2017
DOI: 10.21037/jtd.2017.11.118
|View full text |Cite
|
Sign up to set email alerts
|

Rare causes of hyperbilirubinemia after lung transplantation: our experience at a single center

Abstract: Causes of hyperbilirubinemia after lung transplantation are varied, and the prognosis of patients with hyperbilirubinemia arising from rare causes was poor. Therefore, early evaluation and management of hyperbilirubinemia after lung transplantation is important to improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…As lung transplantation has become more widespread, several complications after lung transplantation have been reported [10][11][12][13]. Recently, we have encountered cases of SSC after lung transplants in our center.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As lung transplantation has become more widespread, several complications after lung transplantation have been reported [10][11][12][13]. Recently, we have encountered cases of SSC after lung transplants in our center.…”
mentioning
confidence: 99%
“…Lung transplantation is the best treatment for patients with end stage pulmonary disease, and the number of lung transplantations has steadily increased [10][11][12][13].…”
mentioning
confidence: 99%
“…Due to lack of consensus in the thoracic transplant literature, work to build a standardized, reproducible definition of postoperative liver dysfunction remains an area of active investigation. [5][6][7] No comprehensive definition currently exists for liver dysfunction in the Additionally, MELD scoring and its variations for anticoagulated patients may be used to identify abnormalities in liver function. 37,38 While still a powerful tool, the efficacy of MELD in predicting the progression of liver disease following lung transplantation remains to be investigated.…”
Section: Definiti On Of P Os Toper Ative Liver Dys Fun C Tionmentioning
confidence: 99%
“…Chan et al 5 reported incidence of hepatic injury/disease by ICD-9 code designation at 6.9% in the postoperative period with 1-, 3-, and 5- Expanded use of cardiopulmonary bypass (CPB) may be associated with development of post-transplant hypoxic hepatitis. 6,39 Catecholamine release following induction of CPB results in up to a 45% reduction in hepatic arterial blood flow and a 20% decrease in hepatic perfusion. 40 The increased hepatic metabolic and physiological demand associated with CPB combined with poor perfusion may overwhelm hepatic protective mechanisms and contribute to the progression of liver disease.…”
Section: Liver Dys Fun C Tion Following Lung Tr Ans Pl Antmentioning
confidence: 99%
See 1 more Smart Citation